Efektivitas online group CBT pada stres dan coping strategy remaja perempuan yang terdampak covid-19 - Ayu Kartika; Mita Aswanti Tjakrawiralaksana (Jurnal Ilmiah Psikologi Terapan, 2021)
The COVID-19 pandemic has prompted the Indonesian government to implement a distance learning system. Changes and uncertainties might deteriorate mental health, especially in female adolescents who were initially prone to experiencing stress based on their developmental stage and gender. This study aims to determine the effectiveness of stress management training with Online Group Cognitive Behavioral Therapy approaches in reducing stress and developing adaptive coping strategies. A total of 8 participants (ages 14-15) were recruited online with the purposive sampling technique. Changes in stress levels and coping strategies were tested using Friedman’s ANOVA test. There was a significant reduction in stress that continued until 1-month follow-up and increased adaptive coping strategies after the intervention (post-test). Participants also reported positive changes in cognition and emotion, including increased belief about their ability to handle stress in the future. However, there was no statistically significant reduction in a maladaptive coping strategy. Additional factors, such as individual differences and interactions with the environment influenced the intervention's effectiveness.